Expression Pattern of Long Non-coding RNAs in Schizophrenic Patients - Safari, Mohammad Reza; Komaki, Alireza; Arsang-Jang, Shahram; Taheri, Mohammad; Ghafouri-Fard, Soudeh (Cellular and molecular neurobiology, 2019)
The role of long non-coding RNAs (lncRNAs) in the pathogenesis of neurological disorders including schizophrenia has been highlighted by independent studies. In the present study, we compared peripheral blood expression of seven lncRNAs between schizophrenic patients and sex- and age-matched controls using quantitative real-time PCR technique. FAS-AS1, PVT1 and TUG1 were significantly down-regulated in schizophrenic patients compared with healthy individuals ( P = 0.007, 0.003 and 0.001, respectively). The association between FAS-AS1 expression and schizophrenia was significant in male subjects aged more than 50 but not in other subgroups. GAS5, NEAT1 and OIP5-AS1 expressions were not significantly different between patients and controls ( P = 0.523, 0.739 and 0.267, respectively). The associations between GAS5, NEAT1 and OIP5-AS1 expressions and schizophrenia were significant in female subjects but not in male subjects. THRIL was up-regulated in schizophrenic patients compared with healthy subjects. Based on the results of bootstraped median regression, and after controlling for the effects of age and sex, the difference in its expression between cases and controls was significant ( P = 0.014), while the interaction between group and sex was not significant. The expression of lncRNAs was not correlated with age in any study subgroups. In addition, we found sex-based pairwise correlations between PVT1 expression and expression levels of OIP5-AS1, THRIL and NEAT1 . We also demonstrated high sensitivity and specificity of GAS5 for diagnosis of schizophrenia in female patients. The current study provides further evidence for the participation of lncRNAs in the pathogenesis of schizophrenia. Future studies are needed to confirm the suitability of lncRNAs as peripheral biomarkers for this psychiatric disorder.